Effect of partial and complete aortic balloon occlusion on survival and shock in a swine model of uncontrolled splenic hemorrhage with delayed resuscitation. Issue 5 (November 2019) - Kauvar, David S.; Schechtman, David W.; Thomas, Sarah B.; Prince, M. Dale; De Guzman, Rodolfo; Polykratis, I. Amy; Kheirabadi, Bijan S.; Dubick, Michael A.
Abstract : BACKGROUND: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is accepted as a resuscitation adjunct and bridge to definitive hemostasis. The ischemic burden of REBOA may be mitigated by a partial REBOA (P-REBOA) strategy permitting longer occlusion times and military use for combat trauma. We evaluated REBOA and P-REBOA in a swine multiple trauma model with uncontrolled solid organ hemorrhage and delayed resuscitation and surgical hemostasis. METHODS: Anesthetized swine (51.9 ± 2.2 kg) had 20 mL/kg hemorrhage and closed femur fracture. Splenic transection was performed and free bleeding permitted for 10 minutes. Controls (n = 5) were hemorrhaged but had no REBOA, REBOA (n = 8) had 60 minutes complete zone 1 occlusion, P-REBOA (n = 8) had 15 minutes complete occlusion and 45 minutes 50% occlusion. Splenectomy was performed and plasma (15 mL/kg) resuscitation initiated 5 minutes prior to deflation. Resuscitation goal was 80 mm Hg systolic with epinephrine as needed. Animals were monitored for 6 hours. RESULTS: An initial study with 120-minute occlusion had universal fatality in three REBOA (upon deflation) and three P-REBOA animals (after 60 minutes inflation). With 60-minute occlusion, mortality was 100%, 62.5%, and 12.5% in the control, REBOA, and P-REBOA groups, respectively ( p < 0.05). Survival time was shorter in controls (120 ± 89 minutes) than REBOA and P-REBOA groups (241 ± 139, 336 ± 69 minutes). Complete REBOA hemorrhaged less during inflation (1.1 ± 0.5 mL/kg) than Control (5.6 ± 1.5) and P-REBOA (4.3 ± 1.4), which were similar. Lactate was higher in the REBOA group compared with the P-REBOA group after balloon deflation, remaining elevated. Potassium increased in REBOA after deflation but returned to similar levels as P-REBOA by 120 minutes. CONCLUSION: In a military relevant model of severe uncontrolled solid organ hemorrhage 1-hour P-REBOA improved survival and mitigated hemodynamic and metabolic shock. Two hours of partial aortic occlusion was not survivable using this protocol due to ongoing hemorrhage during inflation. There is potential role for P-REBOA as part of an integrated minimally invasive field-expedient hemorrhage control and resuscitation strategy.